Aquaculture Carrying Capacity and Water Quality In Indonesian Lakes and Reservoirs - A New Project - A. Bengtson, David (Aquacultura Indonesiana, 2014)
Aquaculture is growing rapidly in Southeast Asia (SEA) and five of the top ten aquaculture producers in the world are countries in SEA. The need to manage aquaculture responsibly is critical. Calculation of aquaculture carrying capacity (ACC) for shared water bodies is necessary for proper management. I review my observations of the needs and capabilities of SEA governments for ACC and then describe a new project in which teams of U.S., U.K. and Indonesian scientists will work on ACC for three Indonesian water bodies – Lake Cirata, Lake Toba and Lake Jatigede.